Practice of Green Accounting Based on GRI 300 Standards at PT Sat Nusapersada Tbk Company - Ilman Rizki; Wiwik Supratiwi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to evaluate the implementation of green accounting principles at PT Sat Nusapersada Tbk and its compliance with the Global Reporting Initiative (GRI) 300 standards in the company's sustainability report. The main focus of this study is to examine how green accounting principles are applied in the company's operations and to identify the challenges faced in meeting the environmental reporting indicators set by GRI 300. A descriptive qualitative approach was used to explore sustainability-related phenomena in this company, using triangulation techniques in data collection from in-depth interviews with the Legal Manager, Investor Relations, and Corporate Secretary, supplemented by an analysis of the company's sustainability report. The research findings indicate that PT Sat Nusapersada Tbk has demonstrated significant commitment to sustainability, implementing green accounting principles covering material, energy, water, emissions, waste, and biodiversity management. However, the main challenge faced by the company is the limited availability of quantitative data for some GRI indicators. Nevertheless, the company has taken positive steps to enhance environmental transparency and accountability through more systematic reporting. The findings of this study are expected to provide insights for other companies in the electronics and manufacturing industry to improve their sustainability reporting and optimize the implementation of green accounting as part of their long-term sustainability strategy.